From the margins to the mainstream : institutionalising minorities in South Asia - Gorringe, Hugo, 1975-; Jeffery, Roger; Waghmore, Suryakant (SAGE Publications India Pvt Ltd, 2016)
Struggle of marginalized community especially Dalits, Muslims and Adivasis to get into the mainstream!